Analisis Penggunaan Media Poster terhadap Minat Belajar Akidah Akhlak Siswa di MAN 1 Pasaman Barat - Hayati, Fitri; Alfurqan, Alfurqan (ALSYS, 2024)
This research aims to determine the use of poster media in class This research uses a qualitative method with the type of library research, the object of this research is class XI students at MAN 1 West Pasaman and the subject of this research is students' interest in learning. Then data is obtained from observation, interviews and documentation to see existing phenomena. The results of this research show that the use of poster media in the Aqidah Akhlak subject in class XI MAN 1 West Pasaman is very interesting and suitable to use because it really helps students in the learning process. Students have high enthusiasm and enjoyment towards the Aqidah Akhlak lesson so that they have determination and a strong will in carrying out learning activities, students have the desire to succeed, there is encouragement and need in learning, there are hopes and aspirations, there is appreciation in learning, there is interesting activities in learning, creating a comfortable learning environment. So it is proven that the use of poster media in learning can increase students' interest in learning.